A Magnetic Data Correction Workflow for Sparse, Four‐Dimensional Data. Issue 10 (12th October 2020) - Aitken, Alan R. A.; Ramos, Lara N.; Roberts, Jason L.; Greenbaum, Jamin S.; Jong, Lenneke M.; Young, Duncan A.; Blankenship, Donald D.
Abstract: High‐quality aeromagnetic data are important in guiding new knowledge of the solid earth in frontier regions, such as Antarctica, where these data are often among the first data collected. The difficulties of data collection in remote regions often lead to less than ideal data collection, leading to data that are sparse and four‐dimensional in nature. Standard aeromagnetic data collection procedures are optimized for the (nearly) 2‐D data that are collected in industry standard surveys. In this work we define and apply a robust magnetic data correction approach that is optimized to these four‐dimensional data. Data are corrected in three phases, with phase 1 operations on point data, correcting for spatiotemporal geomagnetic conditions, then phase 2 operations on line data, adjusting for elevation differences along and between lines and in phase 3, a line‐based leveling approach to bring lines into agreement while preserving data integrity. For a large‐scale East Antarctic survey, the overall median cross‐tie error reduction error reduction is 93%, reaching a final median error of 5 nT. Error reduction is spread evenly between phases 1 and 3. Phase 2 does not reduce error directly but permits a stronger error reduction in phase 3. Residual errors are attributed to limitations in the ability to model 4‐D geomagnetic conditions and also some limitations of the inversion process used in phase 2. Data have improved utility for geological interpretation and modeling, in particular quantitative approaches, which are enabled with less bias and more confidence. Plain Language Summary: Observations of the Earth's magnetic field underpin our knowledge of geology and tectonics and are often among the first data collected in frontier regions. This work focuses on the problems experienced in remote surveys, including observation periods extending over years, and flying heights that vary over kilometers. Conventional approaches are designed for more tightly constrained survey collection and can be inappropriate for these data. A new way to process airborne observations of magnetic field intensity is developed and tested. Applied to a data set in East Antarctica, the data quality is substantially improved and the data better reveals the geology hidden beneath the ice of Antarctica. Key Points: A new approach to correcting four‐dimensional aeromagnetic data is developed and tested with the large‐scale ICECAP data set from East Antarctica Substantial improvements in data quality and reliability are seen and error thresholds are well defined These improvements in data quality support the investigation of subglacial geology and tectonics in magnetic data